2023
DOI: 10.1187/cbe.22-07-0149
|View full text |Cite
|
Sign up to set email alerts
|

Scientist Spotlights in Secondary Schools: Student Shifts in Multiple Measures Related to Science Identity after Receiving Written Assignments

Abstract: Secondary student outcomes after completing at least three Scientist Spotlight assignments were investigated through multi-school collaborations. Across demographics, students significantly increased relatability to and nonstereotypes about scientists. Larger pre–post shifts in students’ relatability to scientists correspond to in-class discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Rather, to engage students, and especially those with excluded identities, it is critical we also humanize scientists. Instructors can enact this change by implementing existing humanizing resources in their courses, such as DataVersify (21,22), Project Biodiversify (23), Scientist Spotlights (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), BioGraphI, Story Collider Podcast, and SACNAS Biography Project. These curricular materials all vary widely in how they incorporate humanizing information, differing in the amount of information included and the way that information is conveyed (i.e., through text, audio, video).…”
Section: What Do Students Relate To?mentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, to engage students, and especially those with excluded identities, it is critical we also humanize scientists. Instructors can enact this change by implementing existing humanizing resources in their courses, such as DataVersify (21,22), Project Biodiversify (23), Scientist Spotlights (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), BioGraphI, Story Collider Podcast, and SACNAS Biography Project. These curricular materials all vary widely in how they incorporate humanizing information, differing in the amount of information included and the way that information is conveyed (i.e., through text, audio, video).…”
Section: What Do Students Relate To?mentioning
confidence: 99%
“…Educators and curriculum developers have worked to combat this false narrative by creating educational materials that highlight scientists from a diversity of backgrounds, intentionally featuring scientists whose identities do not match the dominant stereotype of a scientist (hereafter, counter-stereotypical scientists) (11)(12)(13)(14)(15). Featuring counter-stereotypical scientists in course materials is billed as a scalable, accessible, and easy-to-implement tool that increases the recruitment and retention of students with identities historically and currently excluded from STEM (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists in curricular materials contribute towards the implicit or hidden curriculum, or the subtextual messaging students observe in an achievement environment (such as the science classroom) which signals to some that they naturally belong there and can succeed (4). In curricular materials, student exposure to counterstereotypical scientists lead to significant shifts in students' relatability to scientists (5)(6)(7), perceptions of scientists (5)(6)(7)(8), performance outcomes (7), and gains in science identity measures (6,7). The stereotype inoculation model suggests these positive outcomes are the result of role models functioning as "social vaccines" who increase social belonging and inoculate fellow group members' self-concept against stereotypes (9).…”
Section: Introductionmentioning
confidence: 99%
“…More recent articles also include information about how the focal researcher became a scientist. The PubNavigator biographies were designed based on prior research which has demonstrated that classroom activities that help undergraduate students relate to scientists lead to increased interest in science, reduced stereotypes about scientists, improved academic outcomes, and can promote science identity formation (Aranda et al, 2021; Brandt et al, 2020; Ovid et al, 2023; Schinske et al, 2016; Yonas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%